Identification of Intestinal Parasites in Spinach at Padamara Market, Padamara District - JANG JAYA, NABELA PUTRI; WARDANI, DITA PRATIWI KUSUMA; MUJAHID, IKHSAN; ALMANFALUTHI, MUHAMMAD LUTHFI (Jurnal Medis Islam Internasional, 2024)
Introduction: Vegetables are essential for maintaining human health because they are a great source of vitamins, minerals, fiber, and other nutrients. Most people consume raw vegetables to preserve the nutrients in them. However, raw vegetables have a great potential to spread intestinal parasitic infections. Raw vegetables consumed as fresh vegetables also have the potential to transmit geohelminth infection. Protozoan infections can be transmitted through food and some of these diseases. Objective: This study aims to identify intestinal parasites in spinach at Padamara Market, Padamara District Methods: A total sampling technique was used to collect 20 bunches of spinach at Padamara Market, Padamara District, and the identification of intestinal parasites using the 0.2% NaOH sedimentation method was carried out at the Laboratory of Microbiology and Parasitology, Faculty of Medicine, Universitas Muhammadiyah Purwokerto in April–May 2021. Results: 14 samples (70%) of spinach were positive for intestinal parasites, while 6 samples (30%) were negative for intestinal parasites. The results of intestinal parasite identification found the presence of Ascaris lumbricoides eggs as many as 10 (30.3%), Minute Intestinal Fluke eggs as many as 6 (18.18%), and Entamoeba coli cysts as many as 17 (51.52%). Conclusions: A. lumbricoides egg, Minute Intestinal Fluke eggs, and E. coli cyst were identified in spinach at Padamara Market, Padamara District